STUDI IDENTIFIKASI LANSKAP ALUN-ALUN MERDEKA SEBAGAI IDENTITAS KOTA MALANG - Minggu, Hendrikus; Setyabudi, Irawan; Djoko, Riyanto (Fakultas Pertanian, 2018)
The square is the identity of the city and district in Java in general. The concept of spatial Alun-alun is a symbol of unity of activities that are philosophical-religious, political, economic and cultural, but in its development from the time of the kingdom until now it has always undergone changes and shifts in meaning. Merdeka Square Malang is one of the administrative centers of Malang Regency in the past and also the location of the initial growth of Malang city area. This research aims to internalize and identify landscapes in Merdeka Malang. Identification of the history and development of Malang City Square was carried out to find conservation potential in the plaza area, as a form of respecting cultural heritage, the realization of identity and inheriting historical values. in this study researchers used descriptive analysis methods, synchronous-diachronic analysis of regional development and conservation potential with an assessment of cultural meaning, use value and regional development. The results of the identification of the landscape of the Merdeka Malang square found that Merdeka Malang Square was one of the identities of Malang City. The law on sugar and agrarian policy in 1870 and decentralization in 1903 affected the development of the Merdeka Malang plaza. the development of Merdeka Malang square is very visible in changes in building mass, building style, building functions, changes in land use, physical condition of the square and activities. Based on the history and results of registration and identifying it can be concluded that the Malang Merdeka Square Landscape is one of the identities of Malang City Alun-alun merupakan salah satu identitas kota maupun kabupaten. Konsep keruangan Alun-alun merupakan simbol kesatuan aktivitas yang bersifat filosofis-religius, politis, ekonomis dan kultural, namun dalam perkembangannya dari jaman kerajaan hingga sekarang selalu mengalami perubahan maupun pergeseran makna. Alun-alun Merdeka Malang termasuk salah satu kawasan pusat pemerintahan Kabupaten Malang pada masa lalu dan juga menjadi lokasi pertumbuhan awal wilayah kota Malang. Penelitian ini bertujuan untuk mengiventarisasi dan mengidentifikasi lanskap pada Alun-alun merdeka malang. Identifikasi terhadap sejarah dan perkembangan Alun-alun Merdeka Malang dilakukan untuk menemukan potensi pelestarian pada kawasan alun-alun, sebagai wujud menghargai warisan budaya, perwujudan identitas dan mewarisi nilai sejarah. dalam penelitian ini peneliti menggunakan metode analisis deskriptif, analisis sinkronik-diakronik perkembangan kawasan serta potensi pelestarian dengan penilaian makna kultural, nilai guna serta perkembangan kawasan. Hasil dari identifikasi lanskap menemukan bahwa alun-alun merdeka malang merupakan salah satu Identitas Kota Malang. UU tentang kebijakan gula dan agraria pada tahun 1870 dan desentralisasi pada tahun 1903 berpengaruh terhadap perkembangan kawasan alun-alun merdeka malang. perkembangan alun-alun merdeka malang sangat terlihat pada perubahan massa bangunan, gaya bangunan, fungsi bangunan, perubahan guna lahan, kondisi fisik alun-alun serta aktivitas. Berdasarkan dari sejarah dan hasil iventarisasi serta mengidentifikasi dapat menyimpulkan bahwa Lanskap Alun-alun Merdeka malang merupakan salah satu dari identitas kota malang.